2008
DOI: 10.1103/physreve.77.021911
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic coevolution of cooperative behaviors and network structures

Abstract: This paper aims at understanding coevolutionary dynamics of cooperative behaviors and network structures of interactions. We constructed an evolutionary model in which each individual not only has a strategy for prisoner's dilemma to play with its neighboring members on the network, but also has a strategy for changing its neighboring structure of the network. By conducting evolutionary experiments with various settings of the payoff matrix, we found that the coevolutionary cycles of cooperative behaviors of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…In addition, theoretical studies showed that dynamic changes in network structures can affect the global dynamics of human behaviors (Zimmermann and Eguíluz, 2005;Pacheco et al, 2006;Suzuki et al, 2008), and recent experimental studies with human participants have also shown that cooperative clusters can emerge when participants could modify their network structure of interactions (Fehl et al, 2011;Rand et al, 2011;Wang et al, 2012;Antonioni et al, 2014;Yonenoh and Akiyama, 2014). This is because participants tend to keep cooperative relationships while severing connections with defectors, and thus form cooperative and highly connected clusters in general (Rand et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, theoretical studies showed that dynamic changes in network structures can affect the global dynamics of human behaviors (Zimmermann and Eguíluz, 2005;Pacheco et al, 2006;Suzuki et al, 2008), and recent experimental studies with human participants have also shown that cooperative clusters can emerge when participants could modify their network structure of interactions (Fehl et al, 2011;Rand et al, 2011;Wang et al, 2012;Antonioni et al, 2014;Yonenoh and Akiyama, 2014). This is because participants tend to keep cooperative relationships while severing connections with defectors, and thus form cooperative and highly connected clusters in general (Rand et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several adequate suggestions have been made in the last decade which try to address the conflict of experiment and theory [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. One of these research directions assumed that more sophisticated strategies should be used, which go beyond the simplest unconditional cooperator and defector behaviors [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Evolutionary game theory is a powerful framework to study the problem of cooperation and many efforts have been considered in the past years to clarify the raised problem [4][5][6][7][8][9][10][11][12].…”
mentioning
confidence: 99%